2012
DOI: 10.4172/2161-105x.1000127
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Measurement of Maximal Voluntary Breath-Holding Time in Patients with Obstructive Ventilatory Defects and Normal Controls

Abstract: Background: Breath-holding test has been tested in some clinical scenarios and has proved to be of clinical utility.Objectives: To determine the maximum voluntary breath-holding time in patients with obstructive ventilator defects and in normal subjects and to correlate the breath-holding times with pulmonary function tests. Methods:We conducted a case-control study including patients with obstructive ventilator defects and a control group consisted of volunteers recruited in the same hospital, with normal spi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 9 publications
(13 reference statements)
0
7
1
Order By: Relevance
“…In COPD subjects, even a slight increase in respiratory stimulus may cause a shortening of both the duration of the comfort phase and the duration of total apnea (Nishino, 2009). The mean apnea time reported during our study was 25 ± 8.7 s with values ranging from 10 s to 50 s. This value was not statistically different from that reported by Viecili et al which was 21.6 ± 12.6 s (t = 1.245; p = .214) (Viecili et al, 2012). Maximum apnea time in COPD subjects has been shown to be significantly shorter than in normal subjects (Trembach & Zabolotskikh, 2017).…”
Section: Discussioncontrasting
confidence: 54%
“…In COPD subjects, even a slight increase in respiratory stimulus may cause a shortening of both the duration of the comfort phase and the duration of total apnea (Nishino, 2009). The mean apnea time reported during our study was 25 ± 8.7 s with values ranging from 10 s to 50 s. This value was not statistically different from that reported by Viecili et al which was 21.6 ± 12.6 s (t = 1.245; p = .214) (Viecili et al, 2012). Maximum apnea time in COPD subjects has been shown to be significantly shorter than in normal subjects (Trembach & Zabolotskikh, 2017).…”
Section: Discussioncontrasting
confidence: 54%
“…But the VC is significantly smaller in females than in males. The previous study demonstrated links between pulmonary function, breath-holding time and lung volume in apneic divers (Ferretti et al, 2012;Schagatay et al, 2012), however not in healthy subjects at RV (Viecili et al, 2012).…”
Section: Discussionmentioning
confidence: 87%
“…Each maneuver was repeated three times and the best (highest) values were considered. 15 Forced spirometry was performed in computerized spirometer (Spiro Excel Machine Spirometer, Medicaid System, Chandigarh, India, 2003). Spirometer was prepared, calibrated, and subject was properly instructed.…”
Section: Methodsmentioning
confidence: 99%
“…BHT has been found to be well correlated with FEV 1 and magnitude of dyspnea in patients. 10,11 Owing to their simplicity and cost effectiveness, the CE and BHT have been suggested as reasonable alternatives to spirometry in resource-poor settings with the advantage of independence from technician and machine. 12,13 This study aims to verify this claim.…”
Section: Introductionmentioning
confidence: 99%